What Has Neuroimaging Taught Us on the Neurobiology of Yoga? A Review - van Aalst, June; Ceccarini, Jenny; Demyttenaere, Koen; Sunaert, Stefan; Van Laere, Koen (Frontiers in Integrative Neuroscience, 2020)
Yoga is becoming increasingly popular worldwide, with several implicated physical and mental benefits. Here we provide a comprehensive and critical review of the research generated from the existing neuroimaging literature in studies of yoga practitioners. We reviewed 34 international peer-reviewed neuroimaging studies of yoga using Magnetic Resonance Imaging (MRI), Positron Emission Tomography (PET) or Single Photon Emission Computed Tomography (SPECT); 11 morphological and 26 functional studies, including 3 studies that were classified as both morphological and functional. Consistent findings include increased grey matter volume in the insula and hippocampus, increased activation of prefrontal cortical regions, and functional connectivity changes mainly within the default mode network. There is quite some variability in the neuroimaging findings that partially reflects different yoga styles and approaches, as well as sample size limitations. Hypotheses on the underlying neurobiology derived from the imaging findings are discussed in the light of the potential beneficial effects of yoga.